2022
DOI: 10.1021/acsnano.2c03398
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Organic Zinc-Chelate Formation with Nanoscaled Granular Structure Enabling Long-Term and Dendrite-Free Zn Anodes

Abstract: Aqueous Zn metal batteries suffer from rapid cycling deterioration due to the severe water corrosion and dendrite growth o n Z n a n o d e s . H e r e i n , a h i g h l y a n t i w a t e r Z n xdiethylenetriaminepenta(methylene-phosphonic acid) interface layer with good zinc affinity and special nanoscaled 3D granular structure is designed on Zn metal to address these problems. Experimental results combined with theoretical analysis and COMSOL simulations reveal that the hydrophobic groups in such Zn-based org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 171 publications
(95 citation statements)
references
References 52 publications
2
92
1
Order By: Relevance
“…[10,11] In turn, baneful parasitic reactions drive by-product formation and flagrant dendrite growth. [12] Especially, such issues are serious in conventional liquid electrolytes (LEs) due to the uncontrolled irregular ion migration and high-activity free water. [13,14] The undesired dendrite growth and parasitic reactions degenerate Zn plating/stripping reversibility, thus reducing the coulombic efficiency (CE) and lifespan of ZHMSCs.…”
mentioning
confidence: 99%
“…[10,11] In turn, baneful parasitic reactions drive by-product formation and flagrant dendrite growth. [12] Especially, such issues are serious in conventional liquid electrolytes (LEs) due to the uncontrolled irregular ion migration and high-activity free water. [13,14] The undesired dendrite growth and parasitic reactions degenerate Zn plating/stripping reversibility, thus reducing the coulombic efficiency (CE) and lifespan of ZHMSCs.…”
mentioning
confidence: 99%
“…LSV curves show that the current density of the PAM/CMC/XG/Zn(CF 3 SO 3 ) 2 hydrogel electrolyte prominently lowers relative to LE, suggesting the suppressed HER in the former. 40 Then, we assembled transparent Zn//Zn symmetric cells with different electrolytes to in situ monitor the morphological change in Zn surface during electrodeposition (Fig. 2c and d).…”
Section: Resultsmentioning
confidence: 99%
“…[7,51] From linear scanning voltammetry (LSV) curves (Figure 3c), it is found that the Zn electrode in CGPPHE compared to LE has a smaller current density, and the onset potential of HER increases by ≈70 mV, indicative of the suppressed HER in CGPPHE. [11,27] Profiting from the promotion effect of CGPPHE on confining dendrite growth and parasitic reactions, Zn anodes may possess good electrochemical durability, which is verified by galvanostatic cycling of the symmetric Zn|CGPPHE|Zn cell. As expected, the Zn|CGPPHE|Zn cell can be stably circulated for Small Methods 2023, 7, 2201398 more than 350 h at a current density of 1 mA cm −2 with an area capacity of 1 mAh cm −2 (Figure 3d).…”
Section: Figure 2a-d Confirms Superior Mechanical Properties Of Cgpph...mentioning
confidence: 91%
“…[8,9] More problematically, baneful interfacial side reactions, including hydrogen evolution reaction (HER) and corrosion caused by high-water-activity aqueous solution, exacerbate the dendrite issue. [10,11] At present, Rechargeable aqueous zinc-ion hybrid capacitors (ZHCs) have aroused unprecedented attention because of their high safety, cost effectiveness, and environmental compatibility. However, the intractable issues of dendrite growth and side reactions at the electrode-electrolyte interface deteriorate durability and reversibility of Zn anodes, deeply encumbering the large-scale application of ZHCs.…”
Section: Introductionmentioning
confidence: 99%